Development of Video Learning Media for Elementary School Students - Siagian, Ester Mawar; Listantia, Nora; Sebayang, Yulvitriyani Br; Hutagalung, Vera Kristina; Pertiwi, Santhi (UKInstitute, 2024)
Students' engagement and passion for studying are shaped by their areas of interest. But the fact is that pupils still show very little enthusiasm for studying. Our goal in creating this medium is to provide fourth graders with a high-quality instructional film that will supplement their social studies curriculum. Using the six steps of the ASSURE model—which include student analysis, establishing learning objectives, selecting methods, media, and materials, implementing the model, encouraging student participation, and finally, evaluation and improvement—this learning video media was developed. Students in fourth grade at SDN Pakis V were the topic of this educational film. The creation of this video medium was deemed suitable for use in the fourth grade social studies curriculum. This is derived from the validation findings of specialists in the field of media and materials, as well as students working alone, in small groups, or in big format. The efficacy of this learning video medium was assessed using a posttest after expert and student testing. Students were able to get outcomes higher than the designated KKM when tested using this learning video medium. As a result, creating educational video content is a fruitful endeavour.